(untitled) - Manfoumbi, Christian; Roger, Kevin; Meireles, Martine (Comptes Rendus. Chimie)
Silica precipitation is a ubiquitous but deleterious phenomenon occurring in many hydrometallurgical processes. Indeed, silicon is often released during the dissolution of minerals under acidic leaching conditions. Eventually, it precipitates into a hard-to-filter silica gel, which has prompted some efforts to hinder silica precipitation through pretreatment or extra dilution. However, these approaches are usually either mineral-specific or costly. Here, we propose a disruptive strategy based on controlling the gel’s mesostructure and therefore its filterability. We designed an alternative precipitation pathway consisting of adding extra silicate ions but at basic pH. Using small-angle X-ray scattering, we show that this pathway transforms the network of polymeric silica (“polymer gel”) obtained under highly acidic leaching conditions into a network of dense silica particles (“particle gel”). This structural compaction at the mesoscopic length scale cascades to the macroscale and leads to a drastic improvement in filterability by two orders of magnitude. Furthermore, we demonstrate that this method is generic by applying it successfully to both a model and real ore systems.